Pengaruh corporate social responsibility dan corporate governance terhadap tax avoidance dengan earning performance sebagai pemoderasi - Kezia Josephine; Vianty Adella Santo; Peter Darshan Handoyo (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
The purpose of this study is to test and provide empirical evidence of the influence of independent variables CSR as measured by LN Charitable Donations and CG as measured by LN Board Remuneration on the influence of dependent variables, namely Tax Avoidance as measured by ETR with a moderating variable, namely Earning Performance, which is measured using Return On Assets (ROA). This study will then use multiple regression analysis, which begins with descriptive statistical testing, classical assumption testing, and hypothesis testing. Data testing is assisted by using the E-Views program. The results of this study show that CSR and CG do not affect ETR, and ROA cannot moderate the relationship between CSR and CG on ETR. Public interest statements This research can provide practical benefits for companies, regulators, and academics in understanding and managing effective Tax Avoidance, CSR, and CG practices to improve financial Performance. It can also encourage more responsible business practices and improve corporate accountability in terms of tax compliance and corporate financial transparency.